2019
DOI: 10.1002/adfm.201970060
|View full text |Cite
|
Sign up to set email alerts
|

Metamaterials: Hierarchical Metamaterials for Multispectral Camouflage of Infrared and Microwaves (Adv. Funct. Mater. 10/2019)

Abstract: In article number https://doi.org/10.1002/adfm.201807319, Hyung Hee Cho and co‐workers successfully demonstrate a hierarchical metamaterial (HMM) for multi‐spectral control. The intermediate dielectric layer enables the integration of the microwave absorber and infrared selective emitter. The HMM shows not only the signature control against the microwave and infrared spectra, but also the dissipation of the reduced emitting energy through the undetected band of infrared waves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 0 publications
0
57
0
Order By: Relevance
“…[ 17 ] Moreover, even with higher surface temperatures, their low emissivity endows such black materials with the counter‐intuitive ability to conceal themselves from IR detection due to their limited thermal radiation, showing great potential in multispectral (IR and visible) camouflage assisted by their dark colors. [ 4,18 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 17 ] Moreover, even with higher surface temperatures, their low emissivity endows such black materials with the counter‐intuitive ability to conceal themselves from IR detection due to their limited thermal radiation, showing great potential in multispectral (IR and visible) camouflage assisted by their dark colors. [ 4,18 ]…”
Section: Introductionmentioning
confidence: 99%
“…Visible black inorganic materials with intrinsically low IR emissivity (IR white) are scarce but of great significance for many areas, such as solar energy harvesting, [ 1,2 ] building thermal insulation, [ 3 ] multispectral camouflage, [ 4,5 ] and container package. [ 6 ] For instance, in solar–thermal conversion systems, to maximize the energy conversion efficiency, ideal solar absorbing materials should show perfect light absorption over the broad solar spectrum (0.3–2.5 µm), but simultaneously ultralow mid‐IR absorption/emission (2.5–20 µm) to suppress enormous heat dissipation via thermal re‐radiation (e.g., 0.68 kW m −2 @ 100 °C, 0.68 sun), known as spectrally selective solar absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Subwavelength electromagnetic (EM) wave absorbers are of substantial interest across all parts of the EM spectrum, [ 1–5 ] but are especially important for the MHz and GHz regimes due to their practical significance in stealth technology, [ 6,7 ] heat detection, [ 8 ] sensing, [ 9 ] and communication. [ 10 ] EM wave absorbers are particularly important for self‐driving vehicles or aerial systems, where insufficient protection against stray EM signals may lead to an electronic malfunction, posing a serious risk to human safety.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] These camouflage sheets should be in thermal insulation with the target so that it manifests the same temperatures as that of the background. Studies have reported on emissivity manipulation using paints, [ 17 ] metamaterials, [ 18–24 ] photonic crystals, [ 25–28 ] nanoantennas, [ 29 ] plasmonic structures, [ 30–32 ] phase change materials, [ 33–40 ] graphene, [ 41–43 ] and semiconductors. [ 44,45 ] Most current designs suffer from high specular reflectivity owing to low emissivity.…”
Section: Introductionmentioning
confidence: 99%